Assessing Antecedents of Socially Responsible Supplier Selection in Three Global Supply Chain Contexts. Issue 6 (December 2014) - Griffis, Stanley E.; Autry, Chad W.; Thornton, LaDonna M.; Brik, Anis ben
ABSTRACT A number of highly publicized, controversial lapses in social responsibility within global supply chains have forced managers and scholars to reexamine long‐held perspectives on supplier selection. Extending Carter and Jennings' department‐level study of purchasing social responsibility, our research assesses the role of supply managers' ethical intentions and three key antecedents that drive socially responsible supplier selection. Comparing evidence from firms operating in China, the United States, and the United Arab Emirates, we identify three key drivers of supply managers' ethical intentions and examine both their direct and indirect impacts on socially responsible supplier selection. We find differential support for the predictor relationships on supply manager ethical intentions across national contexts and mediated versus nonmediated models. These observations bear important implications for firms conducting global supply management.